Development of a Chef Uniform Ethics Learning Kit Using Augmented Reality (AR) for Hearing Impaired Students in Polytechnics - Nurul Yusnainy Yusof,; Ismail, Mohd Erfy; Zuan Azhary Mohd Salleh,; Irwan Mahazir Ismail,; Ahmad Zaki Mohamad Amin, (Online Journal for TVET Practitioners, 2025)
Hearing-impaired students face difficulties in understanding the ethics of wearing the chef uniform due to limited communication, lack of standardized sign language terms, and insufficient interactive teaching aids. These challenges reduce their understanding and motivation in learning, highlighting the need for more visual and engaging learning tools. The purpose of this study is to develop a chef uniform ethics learning kit using Augmented Reality (AR) for hearing-impaired students, with a focus on enhancing their visualization, understanding, and motivation through a more interactive and accessible learning experience. The study employs a Design and Development Research (DDR) approach and uses the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model as the instructional design framework. The sample consists of 10 hearing-impaired students enrolled in their second semester of the “Sijil Khas Operasi Katering” program at Politeknik Ibrahim Sultan (PIS), Johor. The findings indicate that the use of the AR-assisted learning kit significantly improves the visualization, understanding, and motivation of hearing-impaired students in understanding chef uniform ethics. The levels of visualization, understanding, and motivation of hearing-impaired students demonstrated high achievements after using the AR-assisted learning kit. Additionally, no significant differences were found between male and female hearing-impaired students, suggesting that the AR-assisted chef uniform ethics learning kit benefits all hearing-impaired students equally, regardless of gender. The results of this study highlight the potential of AR in supporting inclusive education and improving learning outcomes for students with special needs, offering an innovative approach for future educational tools in vocational programs. In conclusion, this study emphasizes the positive impact of AR in creating an inclusive, engaging, and effective learning environment for hearing-impaired students, in alignment with the goals of inclusive education in Malaysia.